Air-oxidation of FeCoNiCr-based quinary high-entropy alloys at 700–900 °C. (June 2017) - Kai, Wu; Li, C.C.; Cheng, F.P.; Chu, K.P.; Huang, R.T.; Tsay, L.W.; Kai, J.J.
Highlights: The oxidation of three high-entropy alloys was studied in dry air at 700–900 °C. The oxidation kinetics of all the alloys followed the parabolic rate law. Multiple scales formed on the alloys were strongly composition-dependent. Abstract: The oxidation of three quinary equimolar high-entropy alloys, containing FeCoNiCrAl, FeCoNiCrMn, and FeCoNiCrSi was studied in dry air at 700–900 °C. The Mn-containing alloy was single-phase, while both Al- and Si-containing alloys were dual-phase. The oxidation kinetics of all the alloys followed the parabolic rate law, regardless of temperature and alloy composition. The oxidation rates of both Al- and Si-containing alloys were lower than those of the quaternary FeCoNiCr alloy, while those of the Mn-containing alloy went to an opposite direction. Multiple scales formed on the alloys were strongly composition-dependent.